(untitled) (Reflection and Critique Law Magazine, 2026)
This study aimed to analyze the process of the securitization of terrorism as shaped by the United States’ agenda and its impacts on the understanding and classification of social movements and actions in Brazil. It sought to investigate how U.S. influence on the political-institutional construction of the concept of terrorism reverberates in the Brazilian context, particularly through the incorporation of security frameworks into the legal system and state practices. To this end, the study examined the conceptualization of terrorism in light of the U.S. experience, as well as the Brazilian normative framework related to the issue, with emphasis on the National Security Law and the Anti-Terrorism Law. Furthermore, the research considered the transnational dimension of the circulation of securitization narratives and rationalities, highlighting how such conceptions have been appropriated within the Brazilian political landscape, especially in recent contexts marked by the intensification of debates on internal order and the notion of the “internal enemy.” Methodologically, the research employed a bibliographic and documentary approach based on primary and secondary sources, complemented by the analysis of data provided by the Ministry of Defense and information obtained through the Freedom of Information Law, enabling the development of descriptive statistics and the construction of an analytical overview. Finally, emblematic cases that occurred in Brazil in recent years were analyzed in order to assess the extent to which certain actions and social movements were framed as security threats or terrorist practices, even when they did not legally constitute terrorism.